(untitled) (Meridiano 47 - Journal of Global Studies, 2017)
Calls for Multilateral Nuclear Approaches (MNAs) have been raised due to growing risks that the expansion of the nuclear power sector poses to a strained international non-proliferation regime. However, MNAs based on comprehensive arrangements lacks feasibility when proposing to divide the world into nuclear fuel suppliers and fuel clients. The growing thirst for energy security, besides the need for technological independency and sovereign access to international nuclear fuel markets are some of the factors undermining the credibility of MNAs as non-proliferation tools.